Programmable Spin–Orbit‐Torque Logic Device with Integrated Bipolar Bias Field for Chirality Control. (3rd March 2020) - Lim, Gerard Joseph; Chua, Daniel; Gan, Weiliang; Murapaka, Chandrasekhar; Lew, Wen Siang
Abstract: Driven by the need to address both the von Neumann bottleneck and scaling limits predicted by Moore's law, spintronic devices have been shown to be strong contenders for logic‐in‐memory applications. While several field‐free spin–orbit torque (SOT)‐driven logic devices have been proposed, their operation typically requires additional initialization or reset pulses, the exchange‐coupled canted spins reduce both anomalous Hall sign‐to‐noise ratio as well as thermal stability of the ferromagnetic layer, and device‐to‐device variation in exchange coupling strength is expected. A reconfigurable SOT‐driven logic device using a double Hall cross structure with an integrated bias field line for the generation of a local bias field is experimentally demonstrated. The on‐chip bipolar bias field can be toggled to flip the SOT‐induced switching chirality, and to assist with deterministic SOT magnetization switching, thereby enabling on‐the‐fly reconfigurability of the logic device to function as one of the several possible logic gates, e.g., AND, NOR, XNOR, XOR, NIMP, and converse NIMP. It is then shown through compact‐modeling and circuit simulation that the applications of such reconfigurable logic devices can be further expanded to build half‐adders. Abstract : A reconfigurable spin–orbit‐torque‐driven logic device with an integrated bias field line is presented. The locally generated bias field enables chirality control of the current‐induced magnetization switching, allowing the device to perform various logic‐gate functions. A compact model of the logic device is also used to demonstrate the logic functionality for half‐adder operations.